Changing roles of propagule, climate, and land use during extralimital colonization of a rose chafer beetle - Horak, Jakub; Hui, Cang; Roura-Pascual, Núria; Romportl, Dusan (Die Naturwissenschaften, 2013)
Regardless of their ecosystem functions, some insects are threatened when facing environmental changes and disturbances, while others become extremely successful. It is crucial for successful conservation to differentiate factors supporting species' current distributions from those triggering range dynamics. Here, we studied the sudden extralimital colonization of the rose chafer beetle, Oxythyrea funesta, in the Czech Republic. Specifically, we depicted the range expansion using accumulated historical records of first known occurrences and then explained the colonization events using five transformed indices depicting changes in local propagule pressure (LPP), climate, land use, elevation, and landscape structure. The slow occupancy increase of O. funesta before 1990 changed to a phase of rapid occupancy increase after 1990, driven not only by changes in the environment (climate and land use) but also by the spatial accumulation of LPP. Climate was also found to play a significant role but only during the niche-filling stage before 1990, while land use became important during the phase of rapid expansion after 1990. Inland waters (e.g., riparian corridors) also contributed substantially to the spread in the Czech Republic. Our method of using spatially transformed variables to explain the colonization events provides a novel way of detecting factors triggering range dynamics. The results highlight the importance of LPP in driving sudden occupancy increase of extralimital species and recommend the use of LPP as an important predictor for modeling range dynamics.
Keywords: fyziologie rostlin; Plant Physiological Phenomena; brouci; Česká republika; Animals; Coleoptera; časové faktory; Population Dynamics; podnebí; Climate; zvířata; populační dynamika; Time Factors; Czech Republic